The impact of Internet use on the quality of life of elderly people living in community homes under the background of smart elderly care - He, Xiangni; Sutunyarak, Chonlavit (Environment and Social Psychology, 2025)
An investigation and analysis of the quality of life of elderly people aging at home in the community in Chengdu was conducted, utilizing Maslow's hierarchy of needs theory, the theory of rational behavior, the Technology Acceptance Model (TAM), the theory of intergenerational solidarity, and the theory of health-related quality of life. The primary objective was to ascertain the critical factors influencing the quality of life of elderly people aging at home in the community and to develop a quality of life model. A causal model was developed and empirically tested to examine the impact of Internet use on elderly quality of life. A survey of 435 elderly people aged 60 and above residing in Chengdu revealed the following: 1) Internet use and quality of life exhibited a significant positive correlation ; 2) Intergenerational relationships, self-assessed health, and social support served as significant mediators; 3) Mediation effects were confirmed. The results confirmed all research hypotheses. They elucidated the mechanism by which Internet use enhances older adults' quality of life, primarily through fortifying intergenerational relationships, elevating self-assessed health, and broadening social support.